2020
DOI: 10.1039/d0ra08745a
|View full text |Cite
|
Sign up to set email alerts
|

Strain-enhanced giant Rashba spin splitting in ultrathin KTaO3 films for spin-polarized photocurrents

Abstract: Strong Rashba effects at semiconductor surfaces and interfaces have attracted attention for exploration and applications. We show with first-principles investigation that applying biaxial stress can cause tunable and giant Rashba effects in ultrathin KTaO3 (KTO) (001) films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…It is known that the strain can induce both the bulk and structure inversion asymmetries, which can give rise to the Dresselhaus and Rashba spin-orbit interaction induced momentum (k)-dependent spin splitting. [65][66][67][68][69][70][71] In our case, since the lattice strain in the Cd 3 As 2 films is maximal near the interface with the GaAs substrate, and relaxes gradually with the increase of thickness, implying that there exists a strain gradient in our samples. The thinner the film, the larger the strain gradient will be expected.…”
Section: Resultsmentioning
confidence: 65%
“…It is known that the strain can induce both the bulk and structure inversion asymmetries, which can give rise to the Dresselhaus and Rashba spin-orbit interaction induced momentum (k)-dependent spin splitting. [65][66][67][68][69][70][71] In our case, since the lattice strain in the Cd 3 As 2 films is maximal near the interface with the GaAs substrate, and relaxes gradually with the increase of thickness, implying that there exists a strain gradient in our samples. The thinner the film, the larger the strain gradient will be expected.…”
Section: Resultsmentioning
confidence: 65%
“…Bareille et al [185] observed a 2DEG at the (111) surface of KTO, confined to the (111) bilayer of Ta atoms, which form a honeycomb lattice in this plane. The ARPES measurements showed only one sub-band with the effective mass m* = 0.3m e , which was taken to imply that the 2DEG was formed by itinerant conduction electrons confined to the reconstructed subsurface layers.…”
Section: Band Structure Modification Due To Surface Conductivity: Arp...mentioning
confidence: 99%
“…For KTO(001) thin films, there are large Rashba energy splitting due to the spin-orbit coupling (SOC) in Ta-5d xz and 5d yz bands, but the SOC has little effect on Ta-5d xy bands [14,37]. Here, the 2DEG consists of Ta-5d xy states and the 2DHG O-2p x /p y states, and therefore the SOC effect is little on electronic structures of the 2DEG and 2DHG.…”
Section: B Interfacial 2d Electron and Hole Gasesmentioning
confidence: 99%